The recovery of upper limb function and postoperative pain in children with lateral humeral condyle fractures were examined retrospectively in relation to the effects of brachial plexus block given in conjunction with general anesthesia - Fan Li; Qiao Yang; Jinrong Yi; Aiqiong Chen (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective To assess in retrospect the effects of brachial plexus block and general anesthesia on children with lateral humeral condyle fractures in terms of postoperative pain and return of upper limb function. Methods Randomly allocated to either the control group (n = 51) or the study group (n = 55) were children with lateral humeral condyle fractures who were admitted to our hospital between October 2020 and October 2021, depending on the surgical anesthetic technique used. The research group had internal fixation surgery with brachial plexus block in addition to anesthesia on the basis of the control group, whereas both groups of children underwent the procedure with general anesthesia alone. Postoperative pain degree, upper extremity functional recovery, occurrence of adverse reactions, etc. Results The study group had shorter mean times for surgery, anesthesia, propofol dose, return to consciousness, and extubation than the control group did at every measure of statistical significance. The T2 heart rate (HR) and mean arterial pressure (MAP) were both significantly lower than the pre-anesthesia HR and MAP, and the T1, T2, and T3 HR and MAP were all significantly lower in the study group compared to the control group (P < 0.05). The difference between the SpO2 values at T0 and T3 was not statistically significant (P > 0.05); the VAS scores at 4 h, 12 h, and 48 h after surgery were higher than those at 2 h after surgery, and reached the peak at 4 h after surgery; within 2 h, 4 h, and 12 h of surgery At 48 h, the study group had substantially lower VAS ratings than the control group (P < 0.05). Post-treatment Fugl–Meyer scale scores were considerably higher across the board compared to pre-treatment levels in both groups. When compared to the control group, individuals who participated in the flexion-stretching coordinated exercise and the separation exercise had significantly better ratings. Electrocardiogram, blood pressure, respiratory circulation, and hemodynamic parameters all remained within normal limits during the surgical procedure. The study group had a 9.09% reduced incidence of adverse events compared to the control group. 19.61% (P < 0.05). Conclusion When used in conjunction with general anesthesia, brachial plexus block can help children with lateral humeral condyle fractures regulate perioperative signs, maintain their hemodynamic level, lessen postoperative pain and unpleasant reactions, and improve the function of their upper limbs. Functional recovery, with high safety and effectiveness.